A remark on certain p-valent functions - M. K. Aouf; H. E. Darwish (International Journal of Mathematics and Mathematical Sciences)
The object of the present paper is to prove an interesting result for certain analytic and p-valent functions in the unit disc U={z:|z|<1}.